2017
DOI: 10.1016/j.iccn.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of nurse observations of symptoms in infants at end-of-life in the neonatal intensive care unit

Abstract: Objectives Assessment and management of symptoms exhibited by infants can be challenging, especially at the end-of-life, because of immature physiology, non-verbal status, and limited symptoms assessment tools for staff nurses to utilize. This study explored how nurses observed and managed infant symptoms at the end-of-life in a neonatal intensive care unit. Research Methodology/Design This was a qualitative, exploratory study utilizing semi-structured face-to-face interviews, which were tape-recorded, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…In a number of studies, healthcare professionals stated that access to specialist support, for example, from a paediatric palliative care team, would be favourable for paediatric symptom management. 24,35,54,77 In three studies, healthcare professionals had access to either a specialist paediatric palliative care team or support from other colleagues, and this was viewed as beneficial for effective symptom management. 52,67,76 In one study, the involvement of a palliative care team was delayed by physicians, who were concerned about families readiness for palliative care, the association of 'palliative' with 'death' and the fear of negatively impacting the physician-family relationship.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, healthcare professionals stated that access to specialist support, for example, from a paediatric palliative care team, would be favourable for paediatric symptom management. 24,35,54,77 In three studies, healthcare professionals had access to either a specialist paediatric palliative care team or support from other colleagues, and this was viewed as beneficial for effective symptom management. 52,67,76 In one study, the involvement of a palliative care team was delayed by physicians, who were concerned about families readiness for palliative care, the association of 'palliative' with 'death' and the fear of negatively impacting the physician-family relationship.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…34,39 In line with this, healthcare professionals with more experience reported greater confidence in treating pain 33 and this was associated with less fatigue in children. 71 A lack of experience or exposure to certain conditions meant that healthcare professionals voiced difficulties in managing rare and/or progressive conditions 48 and in recognising and treating symptoms 35,52 sometimes due to a lack of guidance or evidence (Q34, Q35). 48 Studies found improvements in healthcare professionals' comfort, confidence or knowledge following training or education aimed at improving end-of-life symptom management.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…The evaluation is largely reliant on clinician and family perception of symptoms. A recent qualitative exploratory study interviewed NICU nurses about the EOL care their patients received (32). While small, this study displayed themes of uncertainty, discomfort, and chaos.…”
Section: Assessment Of Symptomsmentioning
confidence: 99%
“…Parents may perceive their baby is distressed by physical changes they observe during the dying process. They often equate these changes with pain or discomfort (32,44,45). As symptom assessment has a component of subjectivity, there can be differing opinions from those interacting with the baby.…”
Section: Parent Perceptionmentioning
confidence: 99%
See 1 more Smart Citation